DIFFICULT‐TO‐TREAT PEDIATRIC OBSESSIVE‐COMPULSIVE DISORDER: FEASIBILITY AND PRELIMINARY RESULTS OF A RANDOMIZED PILOT TRIAL OF d‐CYCLOSERINE‐AUGMENTED BEHAVIOR THERAPY. Issue 8 (30th May 2013) - Farrell, Lara J.; Waters, Allison M.; Boschen, Mark J.; Hattingh, Laetitia; McConnell, Harry; Milliner, Ella L.; Collings, Nigel; Zimmer‐Gembeck, Melanie; Shelton, Doug; Ollendick, Thomas H.; Testa, Chris; Storch, Eric A.
<x xml:space="preserve">Abstract</x> Background This study examined the feasibility and preliminary effectiveness of d‐cycloserine (DCS)–augmented cognitive behavioral therapy (CBT) for children and adolescents with difficult‐to‐treat Obsessive Compulsive Disorder, in a double‐blind randomized controlled pilot trial (RCT). Methods Seventeen children and adolescents (aged 8–18 years) with a primary diagnosis of OCD, which was deemed difficult‐to‐treat, were randomly assigned to either nine sessions of CBT including five sessions of DCS‐augmented exposure and response prevention (ERP) [ERP + DCS] or nine sessions of CBT including five sessions of placebo‐augmented ERP [ERP + PBO]. Weight‐dependent DCS or placebo doses (25 or 50 mg) were taken 1 hour before ERP sessions. Results At posttreatment, both groups showed significant improvements with 94% of the entire sample classified as responders. However, a greater improvement in the ERP + DCS relative to the ERP + PBO condition was observed at 1‐month follow‐up on clinician‐rated obsessional severity and diagnostic severity, and parent ratings of OCD severity. There were no changes across time or condition from 1‐ to 3‐month follow‐up. Conclusions In this preliminary study, DCS‐augmented ERP produced significant improvements in OCD severity from posttreatment to 1‐month follow‐up, relative to a placebo control condition, in severe and difficult‐to‐treat pediatric OCD. The significant effect on obsessional severity suggests that DCS augmentation might be associated with enhanced modification of obsessional thoughts during ERP, and warrants further investigation.